Improving early running-in wear characteristics for dental lithium disilicate glass-ceramics by ion-exchange. (February 2022) - Men, T.J.; Chai, Z.G.; Li, X.C.; Li, D.; Wang, F.; He, L.; Zhang, S.F.; Meng, M.
Abstract: Objectives: This study examined the effects of Li + →Na + ion-exchange on the early wear performance of dental lithium disilicate (LD) glass-ceramics. Methods: Specimens with different shapes were prepared using IPS e.max Press as the LD glass-ceramics. Ion-exchange was conducted by placing polished specimens in molten salt containing 25% NaNO3 and 75% KNO3 at 385 °C for 16 or 64 h. The ion-exchanged specimens were analyzed using X-ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDS) to investigate the structure and the elemental distribution. Thereafter, the specimens were tested for flexural strength, Vickers hardness, and fracture resistance. A portion of the specimens were tested with a pin-on-disk tribometer with 10 N for 40 × 10 4 wear cycles in artificial saliva. Wear analysis of the specimens was performed using a 3D profilometer and analyzed with one-way analyses of variance and Tukey's post hoc pairwise comparisons. Worn surfaces were examined with scanning electron microscopy. Results: The LD glass-ceramics exhibited strong time-dependent wear behavior, with typical running-in and steady wear stages. Ion-exchange treatments at 385 °C for 16 h and 64 h both enhanced the mechanical properties and decreased the wear rates of early running-in wear stage. The early wear performance of specimens treated with ion-exchange for long time (64 h) was improved significantly. Conclusion: A thicker ion-exchange layer may be obtained by processing ion-exchange for a long time. This protocol improves the early wear performance of the glass-ceramics effectively. Clinical significance: Dental restorations may fail prematurely due to excessive wear. It is important to improve the early wear performance of the glass-ceramics. Ion-exchange has the potential to strengthen dental LD glass-ceramics. Understanding the effect of ion-exchange on the early wear performance of glass-ceramics provides insight improving the early wear performance of these restorations.